PERBANKAN ISLAM ARAB SAUDI: KEMAJUAN YANG TERTINGGAL - Shofiah Tidjani (Arabic Literature Department, 2015)
The claim of product innovation in Islamic Banking needs a guidance and the strongest regulation which makes realization of subservience syariah (shariah compliance) and it has an ability to fill all over the market need. The Kingdom of Saudi Arabia, which is now being the dominant factor in economic and market of Islamic banking toward the gulf area of Arabian Penninsula, shows the fact of the absent of regulation while the condition of Islamic banking is not well-structured. This research aimed to answer the main problems between the fatwa’s authority of banking and the absent of goverment’s regulation. The result of this research is concluded that the biggest challenge that will be faced by Saudi Arabia such as the pressure of globally financial system, the coordination of Islamic Banking monitoring, the centralization of national banking’s fatwa (guidance), and the firmness toward conventionally banking and foreign.